Chilean teenagers faced with Latin American immigration: acculturative profiles, prejudice, cultural self-efficacy and well-being - Mera-Lemp, María José (2021)
The new socio-cultural scenario produced by immigration in schools implies a complex process of psychosocial adjustment. National students must also face diverse and new challenges as a result of immigration, which are linked to the perception and management of cultural differences. This paper aims to identify acculturative profiles in a sample (N = 426) of Chilean secondary school students. Cluster analysis allowed us to find a solution of three acculturative profiles (Tolerant Individualist, Undifferentiated Individualist and Undifferentiated Ethnocentric). Results show that these profiles differ in their levels of Affective Prejudice, Cultural Self-efficacy, and Well-being. These findings stress the importance of promoting social environments which could improve positive intergroup contact to enable the development of intercultural competence from early stages of life.